Complement Factor D as a Strategic Target for Regulating the Alternative Complement Pathway - Barratt, Jonathan; Weitz, Ilene (Frontiers in Immunology, 2021)
The complement system is central to first-line defense against invading pathogens. However, excessive complement activation and/or the loss of complement regulation contributes to the development of autoimmune diseases, systemic inflammation, and thrombosis. One of the three pathways of the complement system, the alternative complement pathway, plays a vital role in amplifying complement activation and pathway signaling. Complement factor D, a serine protease of this pathway that is required for the formation of C3 convertase, is the rate-limiting enzyme. In this review, we discuss the function of factor D within the alternative pathway and its implication in both healthy physiology and disease. Because the alternative pathway has a role in many diseases that are characterized by excessive or poorly mediated complement activation, this pathway is an enticing target for effective therapeutic intervention. Nonetheless, although the underlying disease mechanisms of many of these complement-driven diseases are quite well understood, some of the diseases have limited treatment options or no approved treatments at all. Therefore, in this review we explore factor D as a strategic target for advancing therapeutic control of pathological complement activation.